Integratsionnye protsessy podgotovki kadrov po vidam bor'by i vostochnykh edinoborstv - Igumenov, V. M. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The aim of this paper is to consider the elaborated approach to sustantiate the new content of the educational programme for specialists` training on the kinds of wrestling and eastern single combats, basing on the integrative approach to that problem.